CLASSICAL GUIDANCE SERVICES USING WINDOW SHOPPING METHOD TO IMPROVE READING COMPREHENSION OF VOCATIONAL SCHOOL COUNSELORS - Athiyah, Ibnu (IJIET (International Journal of Indonesian Education and Teaching), 2022)
This study aimed to test the effectiveness of classical guidance services using window shopping methods to improve reading comprehension of vocational school counselors. This research was an experimental study with one group pretest-posttets design. Research subjects  were vocational school counselors in East Jakarta. The population in this study were all  vocational school teachers, as training participants with a total of 30 people. The sampling technique used was 30 saturated sampling. The research instrument used was a reading comprehension scale with a validity of 0.304 (Pearson Product Moment) and reliability of 0.826 (Alpha Cronbach). Data analysis techniques using paired sample t-test were significant with a statistical test value of -65.619. The results of the study provide an understanding that classical guidance services with the window shopping method was effective in improving reading comprehension of the vocational school counselors.